Math, asked by anne9km2ehakitly, 1 year ago

Factorise: x4 +x2 +1

Answers

Answered by thehelper
843
Factorise this expression using the difference of squares: 
f(x) = x⁴ + x² + 1 
f(x) = (x² + 1)² - x² 
f(x) = (x² + 1 - x)(x² + 1 + x) 
f(x) = (x² - x + 1)(x² + x + 1) 
f(x) = (x² + x + 1)(x² - x + 1)
Answered by pulakmath007
15

x⁴ + x² + 1 = (x² + x + 1)(x² - x + 1)

Given :

The expression x⁴ + x² + 1

To find :

To factorise the expression

Formula :

  • (a + b)² = a² + 2ab + b²

  • a² - b² = ( a + b ) ( a - b )

Solution :

Step 1 of 2 :

Write down the given expression

The given expression is

x⁴ + x² + 1

Step 2 of 2 :

Factorise the expression

We are aware of the identity that

a² - b² = ( a + b ) ( a - b )

Thus we get ,

\displaystyle \sf{  {x}^{4}   +  {x}^{2}  + 1}

\displaystyle \sf{  =  {x}^{4}   + 2 {x}^{2}  -  {x}^{2}  + 1}

\displaystyle \sf{  =  {x}^{4}   + 2 {x}^{2} + 1  -  {x}^{2}  }

\displaystyle \sf{  =  {( {x}^{2} )}^{2}   + 2. {x}^{2} .1+  {(1)}^{2}   -  {x}^{2}  }

\displaystyle \sf{  =  {( {x}^{2} + 1 )}^{2}      -  {x}^{2}  }

\displaystyle \sf{  =  {( {x}^{2} + 1 )}^{2}      -  {(x)}^{2}  }

\displaystyle \sf{  =  ( {x}^{2}  + 1 + x)  ( {x}^{2} + 1 - x )}

\displaystyle \sf{  =  ( {x}^{2}   + x + 1)  ( {x}^{2}  - x + 1 )}

∴ x⁴ + x² + 1 = (x² + x + 1)(x² - x + 1)

━━━━━━━━━━━━━━━━

Learn more from Brainly :-

1. Find the value of the expression a² – 2ab + b² for a = 1, b = 1

https://brainly.in/question/28961155

2. to verify algebraic identity a2-b2=(a+b)(a-b)

https://brainly.in/question/10726280

Similar questions